Creation of an Islamic state between ambition and ignorance - Solihin, Sohirin Mohammad (2010)
It deals with the study on the Muslim hardliners on the concept of jihad as mentioned in Muslim religious text especially the Qur’an and the Sunnah. It studies their vision with regard to the concept of jihad in which, in reality, does not necessarily gives the meaning as the struggle in the battle field. It also critically discusses their vision on underlining concept from etymological aspect as well terminological concept and their main differences with the views of prominent Muslim scholars. Moreover, it also examines the emergence of the jihad movement which is inseparably related with older generation which emerged in the eve of independence. The way how they train new members among the youths, recruitment system, and their loyalty toward the central leadership is also highlighted. In addition, it also discusses the creation of educational and training center of al-zaytun which they regard it as the home of believers which is equal with the Madinan state established during the life of the Prophet Muhammad (pbuh). Another important aspect, it also highlights on the obligatory infaq taken from its members to be collected from any source regardless of lawfulness and unlawfulness simply for the sake of establishing an ideal Islamic government.